Lipid Matrix Nanoparticles: Pharmacokinetics and Biopharmaceutics - S., Doktorovova; E., Gokce; M., Ozyazici; B., Souto E. (Current Nanoscience, 2009)
Lipid matrix nanoparticles, such as solid lipid nanoparticles (SLN) and nanostructured lipid carriers (NLC), have been sought as a useful alternative for formulating poorly soluble drugs intended for several administration routes, e.g. oral, parenteral and topical. These systems are surfaced by a film of surfactant in an aqueous phase, being therefore physicochemically and thermodynamically stable having a mean particle size below 1 μm. The matrix of SLN is solely composed of a pure solid lipid (melting point above 40°C) whereas NLC is composed of a blend of solid and liquid lipids, which must also be solid at both body and room temperatures. The achievements of SLN and NLC as drug carrier systems are due to several advantages, e.g. incorporation of hydrophobic and hydrophilic drug molecules (including peptides and proteins), controlled release, protection of chemically labile drugs, fulfil several prerequisites for an optimum colloidal drug carrier. The present review aims to emphasize the special features of lipid matrix nanoparticles, in particular for controlled release purposes. An overview on pharmacokinetic and biopharmaceutic results achieved by different research groups is given and their parameters are analyzed.
Keywords: topical